2014
DOI: 10.5301/ejo.5000434
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Transplantation in Acute Toxic Epidermal Necrolysis: Histopathologic Changes and Ocular Surface Features after 1-Year follow-up

Abstract: Amniotic membrane transplantation performed for acute TEN reduced inflammation and ocular surface scarring, improved dry eye and squamous metaplasia. and decreased ocular sequelae in the chronic stage. Although further and prospective studies are needed, AMT may be the optimal treatment for acute TEN with severe or moderate ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These diseases are characterized by serious conjunctival damage, with particular harm to the goblet cell population. 25,29 However, patients 16 (Lyell syndrome) and 19 (Stevens-Johnson syndrome), who presented milder conjunctival involvement, showed a significant downregulation of gene expression, thereby corroborating the hypothesis that increased expression of this mucin after treatment is more related to the degree of conjunctival involvement than to the etiology of the disease. In those eyes in which corneal alterations predominated, such as patients with aniridia or with idiopathic limbal deficiency, we did not find significant changes in mucin expression after the treatment with autologous serum eye drops.…”
Section: Discussionmentioning
confidence: 54%
“…These diseases are characterized by serious conjunctival damage, with particular harm to the goblet cell population. 25,29 However, patients 16 (Lyell syndrome) and 19 (Stevens-Johnson syndrome), who presented milder conjunctival involvement, showed a significant downregulation of gene expression, thereby corroborating the hypothesis that increased expression of this mucin after treatment is more related to the degree of conjunctival involvement than to the etiology of the disease. In those eyes in which corneal alterations predominated, such as patients with aniridia or with idiopathic limbal deficiency, we did not find significant changes in mucin expression after the treatment with autologous serum eye drops.…”
Section: Discussionmentioning
confidence: 54%
“…Most recently, a prospective case series by Lopez-Garcia et al on AMT for moderate and severe ocular involvement of TEN showed that the observed clinical improvement in ocular surface condition and visual acuity corresponded with a reduction in squamous metaplasia in corneal and conjunctival cells and increase in goblet cell density over 1 year [13]. This is the first study to demonstrate the beneficial effects of AMT were linked to histological improvements of the ocular surface.…”
Section: Discussionmentioning
confidence: 71%
“…More promising is a paradigm shift towards disease modulation during the acute inflammatory stage. Recent literature reports have shown that early intervention with AMT in the acute phase of SJS/TEN can minimize ocular surface damage [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMT is widely applied in a variety of ocular surface diseases [ 11 12 13 14 15 ]. It is indeed an effective treatment for most nontraumatic acute perforations.…”
Section: Discussionmentioning
confidence: 99%